Characterization of titanium nitride–hydroxyapatite on PEEK for dental implants by co-axis target magnetron sputtering - Boonyawan D. (2017)
© 2016 Elsevier B.V. In this work, the bioactive TiN-HA layer has been prepared by reactive DC magnetron sputtering system with co-axis target configuration on the polyetheretherketone (PEEK) bio-inert material. The proper plasma conditions used to deposit TiN-HA film on PEEK were carried out by the optical emission spectroscopy (OES). The relationship between the chemical composition of plasma to sputtering pressure, discharge voltage, duty cycle and the content of nitrogen gas were considered. The plasma emission intensity raised to the maximum level when the N 2 content was 0.6 sccm. The voltage was ranged about 500–700 V for the sputtering pressure at 3–7 mTorr and reduced to below 500 V when the pressure increased to more than 7 mTorr. The clear as-deposited films with high refractive index were observed and found to reduce surface contact angle as much lower as 10°. X-ray photoelectron spectroscopy (XPS) result revealed TiOH was also formed in the deposited film besides TiO 2 .